Effects of Race, Education Level, and Skin Tone on Perceived Leadership Ability - Birnkrant, Michael Seth (Tufts Archival Research Center, 2005)
The present study focused on the relationships between race, level of education, skin tone, and perceived leadership ability. Eighty Tufts University undergraduates were presented with a photo of a White or Black male with either high or low education levels, and light or dark skin tone. The participants then read a racially neutral speech, and then completed a 13-item questionnaire that investigated the participants' perceptions of the targets' leadership abilities. It was predicted that there would be a significant main difference for race, skin tone, and education level. It was also predicted that there would be a significant interaction between all three variables. A mean difference was found for skin tone, in which the mean difference was higher for light skin tone than dark skin tone. A significant interaction was found between skin tone and level of education, in which only light skinned targets were evaluated differently based on education level. Light skin tone leaders with high education were evaluated more favorably than like skin tone leaders with low education level. The results provide evidence that will support future research in the topic of leadership and race that can help determine what attributes hinder leaders in their political pursuits.